Screening for CLCN5 mutation in renal calcium stone formers patients - Rebelo,Maria Alice P. (2005)
Thirty-five patients (23 males and 12 females), age 35 ± 13 years old, presenting either idiopathic calcium nephrolithiasis, nephrocalcinosis or mild renal failure with idiopathic calcium nephrolithiasis were selected for the analysis of low molecular weight proteinuria and the possible mutations occurrence in the chloride channel gene CLCN5. The urinary ratio of beta2-microglobulin and creatinine (beta2M/Cr) was very high in a transplanted woman with nephrocalcinosis (>3.23 mg/mmol) and slightly high in five patients (>0.052 or < 1.0 mg/mmol) with multiple urological manipulations. Other studied patients showed beta2M/Cr ratio at normal range (0.003-0.052 mg/mmol) without gender difference (p > 0.05). Mutation analysis of CLCN5 gene was performed in 26 patients of 35 selected (11 with idiopathic hypercalciuria; 6 men with normal calciuria; 3 with mild renal insufficiency and 6 with nephrocalcinosis) and was normal in all subjects even in those with abnormal molecular weight proteinuria. Conclusion: CLCN5 gene mutation is not a common cause of kidney stone disease or nephrocalcinosis in a group of Brazilian patients studied.